The Elkington specimen of cathode copper. Issue 4 (2nd October 2018) - Wraith, A. E.; Mackey, P. J.; Horton, R. W.
ABSTRACT: The specimen of cathode copper dated 1880 in the Percy Collection of the Science Museum, London was produced in the world's first copper electrorefinery located at Pembrey in South Wales, based upon the only known application of jar-cell technology patented by James Elkington in 1869. Drill samples were taken and assayed by ICP-MS for a total of 23 impurity elements, of which 12 were considered for the study. Their average aggregate value of about 20 ppm compares very favourably with about 23 ppm for the same impurities in typical modern cathode. The average silver assay, 2.9 ppm Ag, is very low by modern standards, indicating an anode low in silver, possibly associated with low levels of Pb and Sb and relatively high levels of As and Bi. This unusual combination of anode impurities coupled with exceptional cathode purity is discussed in relation to the contemporary conditions in the Welsh copper industry.